‘Overcrowded with tourists’: Guest Books, Postcards, and Other Popular Forms as ‘Micro-Texts’ of Travel Writing - Alan McNee (Cahiers Victoriens et Edouardiens)
The late nineteenth and early twentieth centuries witnessed an expansion and democratization of travel. Yet the voices of the ‘new tourists’ from the working and lower middle classes are rarely heard, with elite accounts continuing to dominate the archive. This article looks at some exceptions, examining the ‘micro-texts’ of guest book inscriptions to recapture the experiences and impressions of ordinary tourists.